2008
DOI: 10.5194/acp-8-2351-2008
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic nitrogen oxide emissions from soils – impact on NO<sub>x</sub> and ozone over West Africa during AMMA (African Monsoon Multidisciplinary Experiment): modelling study

Abstract: Abstract. Nitrogen oxide biogenic emissions from soils are driven by soil and environmental parameters. The relationship between these parameters and NO fluxes is highly non linear. A new algorithm, based on a neural network calculation, is used to reproduce the NO biogenic emissions linked to precipitations in the Sahel on the 6 August 2006 during the AMMA campaign. This algorithm has been coupled in the surface scheme of a coupled chemistry dynamics model (MesoNH Chemistry) to estimate the impact of the NO e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 54 publications
7
66
0
Order By: Relevance
“…In that purpose, a new approach for the calculation of biogenic NO emissions from soils has been developed by Delon et al (2007), in order to use general environmental parameters easily available as inputs. This approach was used at the regional scale to simulate pulse events in the Sahel (Delon et al, 2008) and at the yearly scale at several Sahelian sites Laouali et al, 2012). This approach has been partly inspired by the hole-in-thepipe (HIP) concept, developed by Firestone and Davidson (1989), presenting the environmental parameters which control the variation of trace-N-gases by nitrification and denitrification with different levels of regulation, from proximal (e.g.…”
Section: Modelling Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…In that purpose, a new approach for the calculation of biogenic NO emissions from soils has been developed by Delon et al (2007), in order to use general environmental parameters easily available as inputs. This approach was used at the regional scale to simulate pulse events in the Sahel (Delon et al, 2008) and at the yearly scale at several Sahelian sites Laouali et al, 2012). This approach has been partly inspired by the hole-in-thepipe (HIP) concept, developed by Firestone and Davidson (1989), presenting the environmental parameters which control the variation of trace-N-gases by nitrification and denitrification with different levels of regulation, from proximal (e.g.…”
Section: Modelling Approachmentioning
confidence: 99%
“…While the STEP model was initially designed for 1-D simulations in well-documented study sites, it has also been re- cently used at the regional scale in the Gourma region to produce maps of vegetation biomass by Jarlan et al (2003), and in the Sahelian belt (12 • N-20 • N; 20 • W-35 • E) by Pierre et al (2012) and Pierre et al (2011), to estimate the amount of dust emissions in that region. The NO flux model has also been applied in the region of Niamey, Niger (Delon et al, 2008) to reproduce NO pulses at the beginning of the wet season, and their impact on ozone formation during the AMMA field campaign in 2006. Furthermore, it has been used at the regional scale in the Sahel and in West Africa to calculate NO release to the atmosphere.…”
Section: Limitations and Uncertaintiesmentioning
confidence: 99%
“…The resulting algorithm provides on line biogenic NO emissions and is developed in Delon et al (2007). It is fully coupled to the SVAT model ISBA, and has been previously tested in the 3-D coupled chemistry-dynamics model MesoNH-C (which uses surface scheme ISBA) to reproduce NO pulses after a rain event in Niger (Delon et al, 2008). • N) will be explored in this study.…”
Section: No Biogenic Emission From Soils: Model Characteristicsmentioning
confidence: 99%
“…A regional non-linear regression model was created using observations over Europe relating S NO x to seven climatic and soil condition variables (Delon et al, 2007). Delon et al (2008) updated this model for use over Africa and found a continuous dependence on soil moisture was crucial to correctly represent temporal variability in S NO x .…”
Section: Yl95 and Its Recent Implementationsmentioning
confidence: 99%